Sense Of Community and Academic Procrastination in Students: Sense Of Community dan Prokrastinasi Akademik pada Mahasiswa - Nadia Putri Setyobudi; Effy Wardati Maryam (Academia Open, 2022)
This research was conducted because of the phenomenon where academic procrastination in students with individual characteristics likes to delay doing academic assignments. This study aims to determine whether there is a relationship between sense of community and academic procrastination in Elementary School Teacher Education students at the University of MuhammadiyahSidoarjo. This type of research is quantitative correlational with a population of 891 students. The sample used is 276 students. With the sampling technique proportionate stratified random sampling. Data collection techniques used the Academic Procrastination scale and the Sense Of Community scale. Academic Procrastination scale reliability test of 0.925. The results of the validity test of the Academic Procrastination scale showed as many as 34 valid items from 36 items. The results of data analysis using Correlation product moment showed r = -0.205, p = 0.001 which means the hypothesis is accepted. The higher the sense of community, the lower the Academic Procrastination. The effective contribution of Sense of community to Academic Procrastination is 5.8 percent. Highlights: Relationship: Explore connection between sense of community and academic procrastination in teacher education students. Sample and data collection: 891 students, 276 sample, proportionate stratified random sampling, Academic Procrastination and Sense of Community scales. Findings: Negative correlation (r = -0.205, p = 0.001) found; higher sense of community linked to lower academic procrastination. Sense of community contributes 5.8% to explaining procrastination. Keywords: academic procrastination, sense of community, elementary school, teacher education, quantitative correlational research